Contradictions of Ordered Trust: Trust-based Work and Conflicting Logics in Municipal Care - Håkansson, Helena (Nordic Journal of Working Life Studies, 2022)
This article examines intra-organizational trust and institutional logics in municipal social care services in the setting of a trust-based developmental project. A case study was conducted in a Swedish municipal district. The data consists of 27 semi-structured interviews with care workers, first-line managers, and strategic staff as well as 11 observations. The study adds insights regarding trust in public sector organizations and shows how a strong focus on economic efficiency can relativize trust into a question of financial accountability. The results demonstrate how the governing managerial logic is not only in conflict with but also seems to overrule attempts to establish a more trust-based logic. Moreover, contributing to the institutional logics literature, it further shows how power structures affect institutional logics and how conflicts between logics play out differently at various organizational levels. The prospects of accomplishing a more trust-based governance without larger institutional or organizational changes are hence problematized.